Aktivitas Antioksidan dan Profil Fitokimia Ekstrak Metanol Daun Bauhinia purpurea L. dari Pekanbaru - Haiyul Fadhli; Hefriza Putri (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Antioxidants are important bioactive compounds that play a key role in neutralizing free radicals and preventing oxidative damage to cells. Bauhinia purpurea L., locally known as butterfly tree leaves, has been reported to contain various phenolic and flavonoid compounds with promising antioxidant potential. This study aimed to evaluate the phytochemical content and antioxidant activity of methanolic extract of Bauhinia purpurea L. leaves collected from Pekanbaru. Phytochemical screening revealed the presence of flavonoids, phenolics, terpenoids, steroids, and alkaloids. The total phenolic and flavonoid contents were 50.79 ± 1.82 mg GAE/g and 59.10 ± 13.03 mg QE/g extract, respectively. Antioxidant activity measured by the DPPH method showed an IC₅₀ value of 67.58 µg/mL, indicating moderate antioxidant potential. These results suggest that Bauhinia purpurea leaves from Pekanbaru have potential as a natural antioxidant source for herbal and pharmaceutical product development. Geographic factors and extraction methods play a significant role in determining the bioactive content and antioxidant activity of the extract.